The Impact of Implementing Bank Tax on Banks Listed on the Warsaw Stock Exchange - Kuta, Katarzyna; Rudnicki, Krzysztof (Journal of Finance and Financial Law, 2016)
The article is focused on the determination of the influence of so called bank tax on banks listed on the Warsaw Stock Exchange in Poland. The elaboration is based on the assumption of a great impact of the bank tax on financial results of banks. In the article there are presented both theoretical and empirical finding concerning this subject. The article contains results of authors’ research made on Warsaw Stock Exchange.